Why there is (no) miracles in the New Testament? The magical Mediterranean environment: notes on ancient power and magic - Chevitarese, André Leonardo; Justi, Daniel Brasil (Romanitas - Revista de Estudos Grecolatinos, 2017)
What this article argues and intends is that the fundamental concept to speak of divine men who know and manipulate the cosmic forces (dýnamis) is the power (dýnamis). It is quite evident that in the Mediterranean basin the association between people (divine men, magicians, etc.) and power (dýnamis) conformed an imaginary of magic. It is precisely this association that made the divine man known. Maybe that’s why Gospel of John has avoided its use. The warning here is to give due consideration to the synoptic view of their respective understandings of sēmĕîon, ĕrgŏn, tĕras and dýnamis, on the one hand, and the Johannine vision of sēmĕîon and ĕrgŏn, on the other. Once the warning about the risk of harmonization in the use of the terms and their respective meanings and consequences observed centuries ago of Christian tradition, it is imperative to analyze what role the concept of power plays in the semantic question and, therefore, in its importance for the understanding of Mediterranean mystic experiences in general and paleochristians in particular.
Keywords: Mystic; Religion; Magic; Paleochristianities; Semantics